Economic analysis and policy in underdeveloped countries - Bauer, P. T. (Durham, N.C. : Duke University Commonwealth-Studies Center, 1957)
In the last two decades there has been a great upsurge of interest in the economics of underdeveloped countries. In view of this, the economic study of underdeveloped countries is certain to bear on important issues of policy, and it may possibly make valuable practical contributions. It may also advance economics by extending the range of phenomena over which its hypotheses can be examined and new hypotheses developed.
Includes bibliographical references and index.
hza 02/07/2018
Loans
Keywords: Economic development; Developing countries